Large intra-abdominal seminoma in a left undescended testicle complicated by torsion. (28th March 2018) - Rourke, Elizabeth; Digman, Gilda; Gourley, Eric; Kaushik, Dharam
Abstract : A 39-year-old man presented with a 2-day history of worsening constant, dull diffuse lower abdominal pain with associated constipation and known history of left undescended testicle. He was evaluated at an outside hospital where a non-contrasted CT scan revealed a 20 cm well-circumscribed soft tissue mass within the pelvis. He was referred and further imaging revealed a 12 cm heterogeneous mass with foci of air that appeared to be contiguous with the left spermatic cord. This constellation of findings could represent torsion of undescended left testicle with infarction or underlying malignancy. Tumour markers were only significant for elevated lactate dehydrogenase of 1445. A subsequent ultrasound-guided biopsy of the mass demonstrated seminoma. Surgical resection revealed a large intra-abdominal mass emanating from the left spermatic cord with 270° of torsion. There appeared to be a left atrophic remnant testicle at the base of the mass with final pathology confirming the diagnosis of classic seminoma.